2020
DOI: 10.1186/s12877-020-01874-4
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of stressful life events prior to suicide among the older adults in rural China: a national case-control psychological autopsy study

Abstract: Background There is a lack of evidence concerning the stressful life events experienced prior to suicide which may be associated with an increased suicide risk among Chinese rural older adults. The aim of this study was to identify the pattern of stressful life events prior to suicide among the older adults in China. Methods Twelve counties were randomly selected using two-stage stratified cluster sampling method. Suicide cases aged 60 years and ol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Stressful life events have been associated with an increased risk of suicide. 3 , 7 , 8 , 36 This reflects the importance of paying more attention to stressful life events while undertaking risk assessment and management.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful life events have been associated with an increased risk of suicide. 3 , 7 , 8 , 36 This reflects the importance of paying more attention to stressful life events while undertaking risk assessment and management.…”
Section: Discussionmentioning
confidence: 99%
“…In suicides, the application of the psychological autopsy method can be helpful in determining the manner of death, and in particular, it is necessary to search the scene for the presence of any letters or writings that may be linked to the self-damaging event. In the context of suicides, a crucial role is played by the analysis of the setting and the anamnestic collection of any previous pathologies both of a psychiatric and organic nature with the interview of family members through collaborations with expert psychologists or forensic psychiatrists [36][37][38]. In this case, the analysis of the setting revealed that the family members knew that the man was building explosives and pyrotechnic articles in his home but had never filed a report with the judicial authorities.…”
Section: Discussionmentioning
confidence: 99%
“…The highest suicide rate within the Australian population is among men aged 85 and above, at a rate of 38.3 suicides per 100 000 individuals 9. In 2016, China’s age-standardised suicide rate was 8 per 100 000 individuals; however, suicide rates among the age groups of 60–69, 70–79 and 80 and above were 23.4, 44.0 and 61.3, respectively—approximately 3–8 times higher than the general population’s suicide rate 10. A meta-analysis indicated that among China’s older population, the proportion of individuals with suicidal ideation ranges from 2.2% to 21.5% 11.…”
Section: Introductionmentioning
confidence: 99%